2016
DOI: 10.3892/mmr.2016.5959
|View full text |Cite
|
Sign up to set email alerts
|

Identification of suitable reference genes for BDV-infected primary rat hippocampal neurons

Abstract: Abstract. Borna disease virus (BDV) is a neurotropic RNA virus that infects the limbic system of mammals and results in behavioral disorders. The hippocampus is a core region in the limbic system, which contributes to memory and learning and is important in the regulation of emotion. However, no validated microRNA housekeeping genes have yet been identified in BDV-infected rat primary hippocampal neurons. Proper normalization is key in accurate miRNA expression analysis. The present study used reverse transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…The symptoms are similar to human cognitive and emotional disorders. 33 In this study, SD rats infected with BoDV-1 had a longer escape latency, crossed the platform fewer times, and spent less time in the target quadrant. The results indicated that newborn rats infected with BoDV-1 developed cognitive impairment as adults.…”
Section: Bodv-1 Upregulates Tlr4 Myd88 and Irf5 Expression In The Rat Hippocampusmentioning
confidence: 62%
“…The symptoms are similar to human cognitive and emotional disorders. 33 In this study, SD rats infected with BoDV-1 had a longer escape latency, crossed the platform fewer times, and spent less time in the target quadrant. The results indicated that newborn rats infected with BoDV-1 developed cognitive impairment as adults.…”
Section: Bodv-1 Upregulates Tlr4 Myd88 and Irf5 Expression In The Rat Hippocampusmentioning
confidence: 62%
“…BoDV-1-infection may induce a large spectrum of neurological disorders ranging from immune-mediated acute encephalitis to non-inflammatory behavioral alterations [7,8]. Previous studies demonstrated that BoDV-1 establishes a persistent infection in the hippocampus and limbic lobe of rodents in the neonatal period, which induced cognitive deficits and mental disorders [4,9]. Notwithstanding abundant discussion of BoDV-1-driven pathophysiology, the precise mechanism underlying how BoDV-1 disrupts memory is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…(microRNA 101a). However, this was considered by the final ranking as the most stable reference gene (Mao et al, 2016). With this in mind, the creation of RefFinder is justified, aiming to acquire information of greater validity.…”
Section: Discussionmentioning
confidence: 99%